AN ANALYSIS OF EFL STUDENTS’ DIFFICULTIES IN CATEGORIZING ENGLISH WORD CLASSES BASED ON THEIR MENTAL LEXICON - Bq. Qotrunnada Keisha Ayu; Jumadil; Edi Firman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze EFL students' difficulties in categorizing English word classes based on their mental lexicon at SMKN 5 Mataram. A qualitative descriptive research design was employed involving fifteen tenth-grade students selected through purposive sampling. Data were collected using a Word Categorization Test and semi-structured interviews. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing and verification. The findings revealed that students experienced difficulties in categorizing abstract nouns, morphologically complex words, and words with multiple grammatical functions. The interview results indicated that these difficulties were influenced by reliance on semantic meaning, limited morphological awareness, difficulties in retrieving grammatical information, and weak lexical connections within the students' mental lexicon. Although most students correctly categorized familiar words, they encountered problems when processing unfamiliar or context-dependent vocabulary. The study concludes that the organization of the mental lexicon plays a significant role in students' ability to categorize English word classes accurately. Therefore, English vocabulary instruction should emphasize not only word meanings but also morphological knowledge, grammatical functions, and contextual usage to strengthen students' lexical organization and improve language learning outcomes.